PENGARUH PDB, INFLASI, KURS DAN TINGKAT SUKU BUNGA TERHADAP NERACA PERDAGANGAN INDONESIA - Ilham Tri Murdo; Junaidi Affan (Kajian Ekonomi dan Bisnis, 2021)
Abstract This study is to determine the extent to which the independent variable factors (GDP, Inflation, Exchange and Interest Rates) affect the dependent variable (Trade Balance) in the last 20 years. Quantitative research aims to obtain empirical evidence regarding the effect of the variables of GDP, Inflation, Exchange Rates and Interest Rates on the Trade Balance, and also to test hypotheses to strengthen or even reject the hypothesis. With the following results: GDP has a negative and insignificant effect on the Trade Balance, Inflation has a negative and significant effect on the Trade Balance, the Exchange Rate has no and no significant effect on the Trade Balance, Interest Rates have no and no significant effect on the Trade Balance and GDP, INflation , Exchange and Interest Rates together (simultaneously) have a significant and significant effect on the Trade Balance